Mengejar Eksistensi di Era Digital: Keterkaitan Fear of Missing Out dan Online Self-Presentation pada Gen Z Pengguna TikTok - Fista Naia Ramadian; Agitia Kurniati Asrila (Indo Publishing, 2025)
The high usage of TikTok among Generation Z has the potential to encourage online self-presentation behavior, often accompanied by anxiety about missing out on others' social experiences. This study employed a quantitative approach with a correlational survey method, involving 400 Generation Z respondents who actively upload content to their personal TikTok accounts. The instruments used included the Fear of Missing Out scale adapted from Kurniawan & Utami (2022), and the Online Self-Presentation scale derived from the Presentation of Online-Self Scale (POSS) developed by Fullwood (2015). Data analysis was conducted using the Spearman technique. The results revealed a significant positive relationship between FoMO and self-presentation, indicating that the higher the level of FoMO, the greater the tendency for individuals to engage in online self-presentation. These findings offer important insights into the digital identity dynamics of Generation Z and how social pressure on social media platforms, particularly TikTok, can influence self-presentation behavior.